A Peran Sekretariat Dewan Perwakilan Rakyat Daerah Dalam Memfasilitasi Aspirasi Masyarakat Di Kota Banjar - Maharani, Nita Ospia; Dini Yuliani; Arie Budiawan (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2023)
Based on the results of research conducted by researchers that the role of the Secretariat of the Regional People's Representative Council in facilitating the aspirations of the people in Banjar City has not been implemented optimally, this can be seen based on problem indicators, namely: the uneven distribution of e-aspiration information to secretariat employees, the limited development of technical guidance followed by general functional and still limited adequate human resources in the use of digitization. This study uses a descriptive qualitative approach. Primary data was obtained from interviews with 8 (eight) informants. Data collection techniques used are observation, interviews, literature study, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study that: 1) The results of the study show that the role of the secretariat of the regional people's representative council in facilitating the aspirations of the people in the city of Banjar as a whole has been implemented but not optimal. 2) The obstacles faced are related to the still limited human resources and budgetary aspects, there are limited patterns of relationships that exist between the facilitator and the recipient of the facility, causing miss communication. 3) In an effort to evaluate the facilities that have been provided and add online-based aspiration facilities, as well as improve the quality of human resources for the Secretariat of the Regional People's Representative Council of the City of Banjar.